2015
DOI: 10.1109/jdt.2015.2443374
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light-Emitting Diode (LED) Configuration on Luminance and Color of an Edge-Lit Backlight Unit

Abstract: In this paper, we evaluated quantitative changes in the luminance and the color on the light-exit plane of an LED edge-lit backlight unit (BLU) by systematically controlling the optical properties of individual white LEDs. We placed a light absorbing film and red-green-blue filters to control the white intensity and the color of an individual LED string, respectively. Impacts of this 'defect' LED's optical properties were systematically monitored across the light-exit plane in terms of local distribution of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The edge-lit structure has thinner profiles and is cheaper due to lesser requirement of an LED chip, while the direct-lit structure provides higher brightness, better luminescence efficiency, and potential local dimming abilities. In general, edge-lit BLUs are preferred options for mobile devices, laptop screens, and cell phones due to thickness, weight, and cost (Moon and Oh, 2015).…”
Section: Liquid Crystal Displaymentioning
confidence: 99%
“…The edge-lit structure has thinner profiles and is cheaper due to lesser requirement of an LED chip, while the direct-lit structure provides higher brightness, better luminescence efficiency, and potential local dimming abilities. In general, edge-lit BLUs are preferred options for mobile devices, laptop screens, and cell phones due to thickness, weight, and cost (Moon and Oh, 2015).…”
Section: Liquid Crystal Displaymentioning
confidence: 99%
“…Despite this, it was shown that the extended IAD method estimates volume scattering parameters which predict the scattered intensity distributions of experimental samples with better accuracy. For lighting luminaires and display backlights, luminance is the fundamental quantity to investigate and optimize [15,16]. In addition to the angular information of the scattered light distribution, the luminance also encompasses the spatial information.…”
Section: Introductionmentioning
confidence: 99%